Perspectives on a Global Observing System to Assess Ocean Health - Duarte, Carlos M.; Poiner, Ian; Gunn, John (Frontiers in Marine Science, 2018)
Concern over the deterioration of the oceans has generated a demand for a system able to assess ocean health globally, and approaches to assess ocean health globally and an observing system delivering the data to support this assessment are now being developed. In parallel with public health systems, a system to assess ocean health should evaluate the occurrence and severity of a set of syndromes of concern through a series of indicators composed from a parsimonious set of ecosystem essential ocean variables delivered by a coherent and robust observing system. The development of such approach for the global assessment of ocean health will help inform policies acting upon the drivers causing ocean syndromes and help ensure a healthy ocean for all.